Digital Academic Transcript Development for Thai University - Ruanmanee, Sorapong; Suchaiya, Sasithorn; Pachanatip, Neranuch; Niramitranon, Jitti (Naresuan University Journal: Science and Technology (NUJST), 2023)
The Electronic Transactions Development Agency (ETDA), one of the public organizations under the control of the Thai government, and related departments such as the Ministry of Digital Economy and Society together with University Delegations, jointly developed an electronic message standard for educational transcripts that defines, to international standards, the data structure of electronic messages in XML format, following the UN/CEFACT Guidelines and based on ETDA Recommendation on ICT Standards for Electronic Transactions 25-2563. These standards include XML Naming and Design Rules for CCTS 2.01 Version 2.1 and Postsecondary Electronic Standards Council (PESC). The objective of this standard is to provide Thai educational institutions with internationally accepted standards for effective Academic Digital Transcript preparation and to develop a design methodology and an academic digital transcript (ADT) application to facilitate the production of transcripts and the exchange of data and documents among academic institutions in Thailand. The format of exchanged documents is PDF/A3 files which consist of transcript XML data. These PDF files are signed by digital signature based on PAdES-LTV, the standard method for signing PDF files with a digital signature, and XML files are signed based on the XML Advanced Electronic Signature (XAdES) standard for electronically signing XML documents. This standard was issued in addition to the XML Digital Signature standard issued by the W3C to enable signatures to provide long-term validation and conformity to the format and implementation of XML. The application developed in this project was used to generate 143,160 academic digital transcripts from February 2021-December 2022. The system had 30 (0.02%) error counts, with 99.98% effectiveness, and 5.66 Kbps efficiency of service rates. Keywords: Transcript, PDF/A3, PAdES-LTV, XML, XAdES